Spiritual Well-Being and Peer Social Support with Academic Stress on Student in Boarding School - Khoirudin, Ahmad; Suroso, Suroso; Farid, Muhammad (Yayasan Minang Darussalam, 2023)
This study examines the simultaneous and partial relationship between spiritual well-being and peer social support with academic stress. This study used a quantitative method. The results of the regression test analysis showed that the value was 22.508 and p = 0.000 (p <0.05) which means that spiritual well-being and peer social support with academic stress have a very significant correlation. The results of the partial correlation test between spiritual well-being and academic stress obtained a value of t = 0.104 and p = 0.917 (p > 0.05) meaning that there is no correlation between spiritual well-being and academic stress. While the results of the partial correlation test between peer social support and academic stress obtained a value of t = 5.410 and p = 0.000 (p <0.05), which means that peer social support has a significant negative relationship with academic stress.